Proteomic Identification of Mitochondrial Targets of Arginase in Human Breast Cancer - Singh, Rajan; Avliyakulov, Nuraly K.; Braga, Melissa; Haykinson, Michael J.; Martinez, Luis; Singh, Vikash; Parveen, Meher; Chaudhuri, Gautam; Pervin, Shehla (PLOS ONE, 2013)
We have previously reported arginase expression in human breast cancer cells and demonstrated that the inhibition of arginase by Nω hydroxy L-arginine (NOHA) in MDA-MB-468 cells induces apoptosis. However, arginase expression and its possible molecular targets in human breast tumor samples and potential clinical implications have not been fully elucidated. Here, we demonstrate arginase expression in human breast tumor samples, and several established breast cancer cell lines, in which NOHA treatment selectively inhibits cell proliferation. The over-expression of Bcl2 in MDA-MB-468 cells abolished NOHA-induced apoptosis, suggesting that the mitochondria may be the main site of NOHA’s action. We, therefore, undertook a proteomics approach to identify key mitochondrial targets of arginase in MDA-MB-468 cells. We identified 54 non-mitochondrial and 13 mitochondrial proteins that were differentially expressed in control and NOHA treated groups. Mitochondrial serine hydroxymethyltransferase (mSHMT) was identified as one of the most promising targets of arginase. Both arginase II (Arg II) and mSHMT expressions were higher in human breast tumor tissues compared to the matched normal and there was a strong correlation between Arg II and mSHMT protein expression. MDA-MB-468 xenografts had significant upregulation of Arg II expression that preceded the induction of mSHMT expression. Small inhibitory RNA (siRNA)-mediated inhibition of Arg II in MDA-MB-468 and HCC-1806 cells led to significant inhibition of both the mSHMT gene and protein expression. As mSHMT is a key player in folate metabolism, our data provides a novel link between arginine and folate metabolism in human breast cancer, both of which are critical for tumor cell proliferation.